Jewels / Nur Anisah Sukor and Noor Liana Mohd Aniffa - Sukor, Nur Anisah; Mohd Aniffa, Noor Liana (2022)
Jewels is a start-up venture launches by business partners that are committed to providing a variety of accessories including necklaces, rings, bracelets, chain masks. These are the fashion pieces that every lady should have. Today, accessories are one of the fashion collections that has become a phenomenon amongst millennial Malaysians. Inspired by the current trend, jewel would take the opportunity to sell stylish and trendy jewelry that will suit Malaysians' skin color.